2020
DOI: 10.1093/humrep/deaa198
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal neutrophils eliminate sperm by trogocytosis

Abstract: STUDY QUESTION What is the vaginal polymorphonuclear (PMN) spermicidal mechanism to reduce the excess of sperm? SUMMARY ANSWER We show that PMNs are very efficient at killing sperm by a trogocytosis-dependent spermicidal activity independent of neutrophil extracellular traps (NETs). WHAT IS KNOWN ALREADY Trogocytosis has been described as an active membrane e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Once in the luminal cavity, neutrophils selectively eliminate subsets of sperm by release of NETs 51 and trogocytosis 54 , although the basis of selection remains unclear. Although this is can be viewed as a ‘hostile’ female response to the male gametes 28 , neutrophil-mediated selection of the fittest or most compatible sperm for fertilization may ultimately increase the chances of a given male siring healthy offspring 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Once in the luminal cavity, neutrophils selectively eliminate subsets of sperm by release of NETs 51 and trogocytosis 54 , although the basis of selection remains unclear. Although this is can be viewed as a ‘hostile’ female response to the male gametes 28 , neutrophil-mediated selection of the fittest or most compatible sperm for fertilization may ultimately increase the chances of a given male siring healthy offspring 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The in ammatory response induced by T. vaginalis can cause neutrophilia through serine protease-dependent pathogenesis. Therefore, contact between neutrophils and sperm cells leads to sperm phagocytosis and death [33]. In infertile females with T. vaginalis infection, the levels of C3 and C4 were decreased, while the levels of IgA and serum prolactin in vaginal secretions were increased [34],…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved 62 research articles, seven of them were selected [12,[28][29][30][31][32][33] based on the inclusion and exclusion criteria.…”
Section: Research Articlesmentioning
confidence: 99%
“…Mercer et al [144], by using 3D and 4D live imaging, observed that PMNs kill the parasites in a contact-dependent, NET-independent engulfment process with bites prior to parasite death, i.e., trogocytosis. In addition, Olivera-Valle et al [145] watched that PMN "bites" sperm and quickly reduces its motility (<5 min) and viability (<20 min) after contact with it in the vaginal lumen but with a low impact on the mucosa damage. These observations indicate PMNs can act as vaginal patrolmen for keeping vaginal homeostasis.…”
Section: The Cytotoxicity Of Pmn On the Other Particular Pathogens Anmentioning
confidence: 99%